The role of extracellular volume fraction in predicting left ventricular reverse remodelling and adverse outcomes in patients with non-ischemic cardiomyopathy and reduced left ventricular ejection fraction - Chung, B.K.; Ling, Hwei Sung; Chan, En Ze; Thien, L.K.; Pang, I. X.; LEONG, L. K.; CHIANG, K. H.; Ko, A. T. Y.; Khor, H. K.; Shu, F.E.P.; Ho, K.H.; Chow, H.B.; et al. (Elsevier, 2023)
Cardiac magnetic resonance (CMR) permits the quantification of extracellular volume fraction (ECV) which is a surrogate marker of myocardial interstitial fibrosis. ECV has been shown to predict heart failure (HF) events. Conversely, left ventricular reverse remodelling (LVRR) defined as decrease in chamber volumes and improvement in function, has a positive impact on prognosis. In patients with non-ischemic cardiomyopathy (NICM), the role of ECV in LVRR is not established.